2003
DOI: 10.1073/pnas.0431131100
|View full text |Cite
|
Sign up to set email alerts
|

A role for Z-DNA binding in vaccinia virus pathogenesis

Abstract: The N-terminal domain of the E3L protein of vaccinia virus has sequence similarity to a family of Z-DNA binding proteins of defined three-dimensional structure and it is necessary for pathogenicity in mice. When other Z-DNA-binding domains are substituted for the similar E3L domain, the virus retains its lethality after intracranial inoculation. Mutations decreasing Z-DNA binding in the chimera correlate with decreases in viral pathogenicity, as do analogous mutations in wild-type E3L. A chimeric virus incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
244
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 208 publications
(250 citation statements)
references
References 28 publications
3
244
1
2
Order By: Relevance
“…Likewise, Tyr 177 of Z␣ ADAR1 forms an important interaction in Z-DNA binding, and mutating it to Ala strongly decreases Z-DNA binding (Fig. 1B) (8). When the analogous Tyr 48 of E3L is mutated to Ala (Y48A E3L) due to loss of an important van der Waals contact and a hydrogen bond, the activation activity of E3L is strongly decreased.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Likewise, Tyr 177 of Z␣ ADAR1 forms an important interaction in Z-DNA binding, and mutating it to Ala strongly decreases Z-DNA binding (Fig. 1B) (8). When the analogous Tyr 48 of E3L is mutated to Ala (Y48A E3L) due to loss of an important van der Waals contact and a hydrogen bond, the activation activity of E3L is strongly decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Although E3L accumulates in the nucleus, consistent with previous reports (3,11), its function there is unknown. It has been demonstrated that the E3L N-terminal domain binding to Z-DNA is necessary for pathogenicity in mice (8). Z-DNA-forming sequences are found near the transcription start site of many human genes (14), and negative supercoiling generated behind a moving polymerase during transcription (15) stabilizes Z-DNA formation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations